Evaluation of antimicrobial prescriptions in dogs with suspected bacterial urinary tract disease. (16th August 2021) - Weese, Jeffrey Scott; Webb, Jinelle; Ballance, Dennis; McKee, Talon; Stull, Jason W.; Bergman, Philip J.
Abstract: Background: Antimicrobials are commonly used to treat urinary tract disease in dogs. Understanding antimicrobial use is a critical component of antimicrobial stewardship efforts. Hypothesis/Objectives: To evaluate antimicrobial prescriptions for dogs diagnosed with acute cystitis, recurrent cystitis, and pyelonephritis. Animals: Dogs prescribed antimicrobials for urinary tract disease at veterinary practices in the United States and Canada. Materials and Methods: A retrospective review of antimicrobial prescriptions was performed. Results: The main clinical concerns were sporadic bacterial cystitis (n = 6582), recurrent cystitis (n = 428), and pyelonephritis (n = 326). Amoxicillin/clavulanic acid (2702, 41%), cefpodoxime (1024, 16%), and amoxicillin (874, 13%) were most commonly prescribed for sporadic bacterial cystitis. The median prescribed duration was 12 days (range, 3‐60 days; interquartile range [IQR], 4 days). Shorter durations were used in 2018 (median, 10 days; IQR, 4 days) compared to both 2016 and 2017 (both median, 14 days; IQR, 4 days; P ≤ .0002). Amoxicillin/clavulanic acid (146, 33%), marbofloxacin (95, 21%), and cefpodoxime (65, 14%) were most commonly used for recurrent cystitis; median duration of 14 days (range, 3‐77 days; IQR, 10.5 days). Amoxicillin/clavulanic acid (86, 26%), marbofloxacin (56, 17%), and enrofloxacin (36, 11%) were most commonly prescribed for pyelonephritis; however, 93 (29%) dogs received drug combinations. The median duration of treatment was 14 days (range, 3‐77 days; IQR, 11 days). Conclusions and Clinical Importance: Decreases in duration and increased use of recommended first‐line antimicrobials were encouraging. Common drug choices and durations should still be targets for antimicrobial stewardship programs that aim to optimize antimicrobial use, concurrently maximizing patient benefits while minimizing antimicrobial use and use of higher tier antimicrobials.